2006
DOI: 10.1002/hep.21260
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of hepatic fibrosis in treated genetic hemochromatosis: A study of 36 cases

Abstract: The current study was undertaken to assess whether fibrosis could regress under venesection therapy in patients with C282Y homozygous genetic hemochromatosis. The 36 patients studied were recruited from a subfile of our database consisting of 125 C282Y homozygotes with either severe fibrosis or cirrhosis (F3 or F4 fibrosis stage, respectively, according to the METAVIR grading system). The second liver biopsy was performed for management of liver cancer, extrahepatic surgery, or assessment of liver fibrosis. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
108
0
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 209 publications
(117 citation statements)
references
References 45 publications
1
108
0
8
Order By: Relevance
“…Hepatic fibrosis, and occasionally cirrhosis, can also be reversed by iron removal (43), but cirrhosis in most cases is irreversible and is associated with an increased risk of primary hepatocellular carcinoma. We previously reported that male C282Y homozygotes in the HEIRS Study were more likely to report a history of liver disease at the time of the initial screening examination than were participants without HFE mutations (24).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic fibrosis, and occasionally cirrhosis, can also be reversed by iron removal (43), but cirrhosis in most cases is irreversible and is associated with an increased risk of primary hepatocellular carcinoma. We previously reported that male C282Y homozygotes in the HEIRS Study were more likely to report a history of liver disease at the time of the initial screening examination than were participants without HFE mutations (24).…”
Section: Discussionmentioning
confidence: 99%
“…This could, of course, be merely due to the fact that the disorder was diagnosed at earlier and earlier stages or that better supportive treatment became available for diabetes, cirrhosis, and infections. More compelling is the fact that cirrhosis of the liver seems, on serial biopsy, to improve after phlebotomy treatment is instituted [74][75][76].…”
Section: Treatment Of Iron Overloadmentioning
confidence: 99%
“…Despite correct elimination of the iron burden, insulindependent diabetes will not resolve, and the risk for hepatocellular carcinoma remains if cirrhosis was present prior to venesection therapy. Although regression of cirrhosis is sometimes observed following venesection therapy, 34 whether this decreases the risk for the development of hepatocellular carcinoma requires further study. …”
Section: Results Of Venesectionmentioning
confidence: 99%